Penerapan Kewajiban Konsumen Untuk Membaca Informasi Barang Berupa Makanan Ringan dan Minuman Dalam Rangka Perlindungan Diri Sebagai Konsumen Berdasarkan Undang- Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen Di Kecamatan Sail - Amaliah, Nadhira; Hasanah, Ulfia; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Consumer protection is a term used to describe the Legal Protection givento consumers in their efforts to meet the needs of the things that could harmconsumers themselves. Consumer protection law exists to protect the consumerthemselves. Consumers are required to be critical using product with considering